Antifungal and antiproliferative activities of endophytic fungi isolated from the leaves of Markhamia tomentosa - Mutiat Ibrahim; Nutan Kaushik; Abimbola Sowemimo; Hemraj Chhipa; Trevor Koekemoer; Maryna van de Venter; Olukemi A. Odukoya (Taylor & Francis Group, 2017)
Context: Plants harbor endophytes with potential bioactivity. Markhamia tomentosa (Benth) K. Schum ex. Engl. (Bignoniaceae) is reported to possess antioxidant, anti-inflammatory and anticancer activities. Objective: The antifungal and antiproliferative properties of endophytic fungi extracts and fractions from M. tomentosa were evaluated. Material and methods: Endophytic fungi were isolated from the leaves of M. tomentosa and identified by ITS-rDNA sequence analysis. The antagonistic effect of the fungal strains was investigated against pathogenic fungi viz, Fusarium oxysporum, Sclerotinia sclerotiorium, Rhizoctonia solani, and Botrytis cinerea using the dual culture assay for 5-7 days. Antiproliferative effect of the fungal extracts and fractions (3.91-250 μg/mL) on HeLa cancer cell line was tested and IC50 was calculated. Poisoning food assay and antifeedant activity against the pathogenic fungi and Spodoptera litura larvae, for 7 days and 2 h, respectively, was also tested at concentrations of 250, 500 and 1000 μg/mL. Results: Fungal endophytes Trichoderma longibrachiatum and Syncephalastrum racemosum were isolated from the leaves of M. tomentosa. Isolated endophytic fungal strains and solvent extracts showed MIC value of 1000 μg/mL against tested pathogenic fungi in the dual culture and poisoning food assays. Methanol fraction of S. racemosum isolate showed the most effective antiproliferative activity with IC50 of 43.56 μg/mL. Minimal feeding deterrent activity against S. litura larvae was also observed. Discussion and conclusion: These findings showed that the leaves of Markhamia tomentosa harbor strains of endophytic fungi with promising health benefits, and suggest their antifungal and antiproliferative effects against pathogenic fungi and HeLa cancer cell line.